Studying the Dependence of Layer-by-Layer Snow Density Variability Dynamics upon Intra-Snow Crystal Formation in Snow Cover Evolution - Tentyukov, M. P. (Journal of Environmental Science and Engineering Technology, 2015)
Presentation of the results of testing a snow sampler with a controllable pitch designed for layer-by-layer snow pit studying. Demonstration of the snow cover structural features and diagenetic transformations typical for the winter of 2009-2010. Identification of the snow mass snow pack growth related to intra-snow crystal formation. Discussion of the mechanism of the process and its role in snow cover evolution. The results could be used for interpretation of the snow cover remote sensing data within zonal natural complexes–middle–taiga bilberry spruce forests.